Childbirth Perception in Baby Boomers, Generations X, Y, And Z: A Qualitative Study. - Sercekus, Pinar; Uludag, Elif; Yildirim Goksen, Dicle Filiz; Ozkan, Sevgi (International Journal of Caring Sciences)
Background: Perception of birth is an important factor that can affect caesarean rates and maternal adaptation. Examining birth perception in all generations can reveal positive and negative changes in birth perception from past to present. Aim: The aim of this study was to examine the birth perception of Baby boomers, X, Y and Z generations. Methodology: Forty-six women participated in the study. Data were collected between February and May 2022 via social media platforms using the snowball sampling method. Interviews were conducted by telephone. Two data collection forms were used: The Introductory Information Form and the Semi-structured Interview Form. In this study, qualitative content analysis was performed. Five main themes emerged regarding women's perception of childbirth. They included baby, pain, fear, support, and strength. Baby, pain, and fear were found to be the focus of women's childbirth perceptions in all generations. Results: Five main themes emerged regarding women's perception of childbirth. They included baby, pain, fear, support, and strength. Conclusion: Generations Y and Z had a more negative perception of childbirth due to increased responsibilities towards the baby, and their childbirth perceptions were influenced by social media more. Health personnel should be aware that the perception of childbirth can change based on the general characteristics of generations, and they should revise the healthcare they provide according to the characteristics of future generations.